Characteristics of high protein product-derived from catfish mixed with fermented sweet potato flours and its impact on malnourished rats - Adi, Annis Catur; Salisa, Wizara; Muhammad Taher,; Rifqi, Mahmud Aditya; Rachmawati, Heni (Penerbit Universiti Kebangsaan Malaysia, 2025)
In 2022, Indonesia has prevalence of stunting over 20%. One of the variables that can contribute to stunting is protein deficiency. This issue can be mitigated by providing a sufficient consumption of animal protein. Implementing food formulation as a means of diversifying local food sources is a strategy to address the issue of stunting while improving food security. This study aimed to assure the standard quality, nutritional content, level of consumer acceptance, and the impact of a composite flour made from a combination of catfish and fermented sweet potato, which had been enriched with micronutrients. The research process encompassed several stages: formulation, evaluation of product characteristics and compliance to regulatory standards of food contaminants, nutritional content, hedonic tests by panelists, and animal model as pre-clinical testing. The findings indicated that flour consisted of catfish and fermented sweet potato enriched with micronutrients served as a high-protein mixture (25.35%, while ordinary flour 13%) encompassing a complete range of nutrients. This formulation fulfills the requirements for product standards and ensures food safety. The product meets panelists acceptance (taste rating >3.5 means like) and is a suitable ingredient for various processing methods. In animal model, this product can significantly increase the body weight of malnourished rats (p<0.05). Catfish and sweet potato are potential local foods serving high-protein flour. This flour enriched with micronutrients can further improve the nutritional content, high acceptability, demonstrate optimal characteristics, food contaminants-free, and proven to increase body weight on rats.